2011
DOI: 10.1007/s00380-011-0123-7
|View full text |Cite|
|
Sign up to set email alerts
|

A possible cross-sectional association of serum total bilirubin with coronary heart disease and stroke in a Japanese health screening population

Abstract: Bilirubin is a potent antioxidant, and serum total bilirubin (TB) is reported to be negatively associated with cardiovascular disease (CVD). There has been no report on the association between TB and CVD prevalence in Japanese. The aim of the study is to examine the association between TB and CVD prevalence in a Japanese health screening population. Prevalence of CVD was studied in 3,375 Japanese men and 2,069 Japanese women. Odds ratios (ORs) of each higher quintile of TB using the lowest quintile as the refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…25,26 Also, diminished TB is linked with diabetes mellitus, cardiovascular disease, peripheral artery disease, and stroke, which all are relevant to chronic inflammation. 6,7,27,28 Our results revealed that dyslipidemia is associated with SCI. The results are in line with those of other groups.…”
Section: Discussionsupporting
confidence: 51%
“…25,26 Also, diminished TB is linked with diabetes mellitus, cardiovascular disease, peripheral artery disease, and stroke, which all are relevant to chronic inflammation. 6,7,27,28 Our results revealed that dyslipidemia is associated with SCI. The results are in line with those of other groups.…”
Section: Discussionsupporting
confidence: 51%
“…19,20 Collectively, the evidence from this 18 and other studies [11][12][13][14][15][16][17] supports the possibility that the early measurement of TB levels might be useful to assess the risk of silent cerebral infarction(s) and major stroke and that mildly elevated TB levels might protect from stroke events and from neurological damage in stroke.…”
Section: Targher Risk Of Ischemic Stroke 703supporting
confidence: 58%
“…Low total serum bilirubin is associated with coronary artery calcification (CAC), and with the presence of angiographically documented coronary heart disease (CHD) after adjustment for the established risk factors (26). Men without atherosclerotic cardiovascular disease (CVD) were shown to have higher total bilirubin levels than men with CVD (25).…”
Section: Introductionmentioning
confidence: 99%
“…Men without atherosclerotic cardiovascular disease (CVD) were shown to have higher total bilirubin levels than men with CVD (25). Thus, bilirubin may be a novel negative risk factor of CVD (26).…”
Section: Introductionmentioning
confidence: 99%